2013
DOI: 10.1021/la3043654
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Studies of Electrochemically Controlled Surface Oxidation and Hydrophobicity of Natural Enargite

Abstract: The surface oxidation and hydrophobicity of natural enargite (Cu(3)AsS(4)) and the formation of oxidation species at the mineral surface have been examined by a novel experimental approach that combines electrochemical techniques and atomic force microscopy (AFM). This approach allows for in-situ, synchronized electrochemical control and examination of the oxidative surface morphology of enargite. Combined with ex-situ cryo X-ray photoelectron spectroscopy surface analysis, the surface speciation of enargite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Electrochemical oxidation of enargite at low pH is typified by Cu dissolution and the formation of native sulfur, while at high pH sulfur is expected to oxidize to polysulfide (Sn ) . In a previous study of enargite oxidation at pH 10 and 4, and +869 mV (Plackowski et al 2013) the presence of elemental sulfur at pH 4 was confirmed by comparing the S 2p photoelectron spectra obtained at below -130 °C with that resulting from the same surface after warming to 30 °C. No evidence of S 0 was found at pH 10.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Electrochemical oxidation of enargite at low pH is typified by Cu dissolution and the formation of native sulfur, while at high pH sulfur is expected to oxidize to polysulfide (Sn ) . In a previous study of enargite oxidation at pH 10 and 4, and +869 mV (Plackowski et al 2013) the presence of elemental sulfur at pH 4 was confirmed by comparing the S 2p photoelectron spectra obtained at below -130 °C with that resulting from the same surface after warming to 30 °C. No evidence of S 0 was found at pH 10.…”
mentioning
confidence: 68%
“…Typical cyclic polarization curve for natural enargite at pH 10 obtained using a scan rate of 1 mV/s. The polarization was initiated at 0 mV, returned to the cathodic scan at 1100 mV, switched to the anodic direction at -690 mV, and terminated at 0 mV (Plackowski et al 2013) Figure 10. Eh-pH diagrams for the Cu-As-S-H2O, As-Cu-S-H2O and S-As-Cu-H2O systems at 278K.…”
Section: List Of Figuresmentioning
confidence: 99%
See 3 more Smart Citations